2007
DOI: 10.1086/512970
|View full text |Cite
|
Sign up to set email alerts
|

A 3 Jy Radio Burst at a High Galactic Latitude

Abstract: A radio burst lasting up to 72 hr at a high Galactic latitude was detected by interferometric drift-scanning observation using an eight-element, 20 m diameter fixed spherical dish array at the Waseda Nasu Pulsar Observatory in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…We review several recent discoveries of radio transients with durations between minutes to days (Kuniyoshi et al 2006a;Bower et al 2007;Niinuma et al 2007;Kida et al 2008). We suggest that these radio transients may be generated by a single class of progenitors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We review several recent discoveries of radio transients with durations between minutes to days (Kuniyoshi et al 2006a;Bower et al 2007;Niinuma et al 2007;Kida et al 2008). We suggest that these radio transients may be generated by a single class of progenitors.…”
Section: Discussionmentioning
confidence: 97%
“…These authors reported 11 bright radio transients (and several others were mentioned but without details), with flux density above 1 Jy in the 1.4 GHz band. Ten were singleepoch transients while one was detected on two successive days with flux densities of 1.7 and 3.2 Jy, respectively (Niinuma et al 2007). In each epoch, the transients were detected for about four minutes, which is the drift scanning time, and did not exhibit any significant variation within the observation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with Bower's discovery, 11 radio transients were detected in Nasu sky surveys conducted by the Nasu Observatory Niinuma et al 2007a;Matsumura et al 2007;Kida et al 2008;Matsumura et al 2009;Niinuma et al 2009). The flux density of the transients exceeded 1 Jy at 1.42 GHz, their duration time ranged from minutes to days, and no clear counterparts were observed (see Section 2 for details).…”
Section: Introductionmentioning
confidence: 93%
“…Here, n is the data point and nΔt represents the observation time. Furthermore, we calibrated the receiver gain fluctuation by using our developed gain calibration system after obtaining the data (Niinuma et al 2007a). When a radio source passes an antenna making up the interferometer, a fringe appears in the data.…”
Section: Observation Datamentioning
confidence: 99%